Validation of a Short Questionnaire in English and French for Use in Patients with Persistent Upper Gastrointestinal Symptoms Despite Proton Pump Inhibitor Therapy: The Pass (Proton Pump Inhibitor Acid Suppression Symptom) Test - David Armstrong; Sander JO Veldhuyzen van Zanten; Sharon A Chung; Colin M Shapiro; Sukhjeet Dhillon; Sergio Escobedo; Bijan K Chakraborty; Vijay Mann; Lisa Tanser; Krista Nevin (Canadian Journal of Gastroenterology)
BACKGROUND: The management of persistent symptoms during acid suppression therapy in patients with gastroesophageal reflux disease or dyspepsia might be improved if patient-physician communication regarding the presence and character of these persistent symptoms were facilitated.